2022
DOI: 10.1177/07487304221125363
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Circadian Disruption During Adolescence Interacts With a Genetic Risk Factor to Modify Schizophrenia-relevant Behaviors in a Sex-dependent Manner

Abstract: DTNBP1 is a gene associated with schizophrenia. Postmortem studies found a reduced expression of DTNBP1 in regions associated with schizophrenia in patients’ brains. Sandy (Sdy) mice have a loss-of-function mutation in Dtnbp1 gene, resulting in behavioral deficits and brain changes similar to those seen in patients with schizophrenia. We previously showed that exposing adult Sdy mice to circadian disruption led to an exacerbation of schizophrenia-relevant behaviors. Here we asked whether the interaction betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 82 publications
1
3
0
Order By: Relevance
“…Here, we found interactions between MIA and circadian disruption at the behavioral and microglial level. Our data supports a role for circadian disruption as a risk factor for NDDs, which has already been shown in a genetic mouse model for schizophrenia 35 , 36 . Future research should address the mechanisms that underlie this interaction to inform the development of circadian-based therapies that aim to prevent or mitigate these serious diseases.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Here, we found interactions between MIA and circadian disruption at the behavioral and microglial level. Our data supports a role for circadian disruption as a risk factor for NDDs, which has already been shown in a genetic mouse model for schizophrenia 35 , 36 . Future research should address the mechanisms that underlie this interaction to inform the development of circadian-based therapies that aim to prevent or mitigate these serious diseases.…”
Section: Discussionsupporting
confidence: 89%
“…In many individuals with NDDs, circadian disturbances precede the onset of psychosis 30 , 34 , which supports a role for circadian disruption as a risk factor for NDDs. This hypothesis is reinforced in a genetic mouse model for SCZ, where SCZ-related behaviors worsened after altered light exposure 35 , 36 . If circadian disruption is a risk factor for NDDs, individuals with NDDs may be vulnerable to the effects of environmental circadian disruption (e.g., shift work), in ways that affects the expression of symptoms experienced.…”
Section: Introductionmentioning
confidence: 92%
“…Previous work from our group found that in males, LL exposure during adulthood led to reduced sociability in poly IC exposed mice but had no effect on saline-exposed(35), whereas chronic jetlag exposure reduced sociability in both males and females (33). These data suggest an interplay between prenatal poly IC and LL exposure in males on both anxiety-like behavior and sociability.…”
Section: Discussionmentioning
confidence: 79%
“…Interestingly, in many individuals with SCZ, circadian disruptions precede the onset of psychosis(31, 32), suggesting that circadian disruption may be a risk factor for neurodevelopmental disorders. This hypothesis is supported by some mouse models for SCZ, where SCZ-related behaviors worsened after altered light exposure(33–35).…”
Section: Introductionmentioning
confidence: 68%
“…CJL led to sociability deficits in Sandy mice. Sex‐specific differences were also present, wherein CJL resulted in reduced anxiety‐like behaviour and decreased PPI in males and females, respectively (Cloutier et al, 2022).…”
Section: Circadian Disruption As a Risk Factor For Nddsmentioning
confidence: 99%